Lama bekerja, keikutsertaan pelatihan dan tingkat pendidikan bidan terhadap perilaku pencegahan infeksi - Sri Lestari M.J; Yuni Kusmiyati; Siti Tyastuti (Poltekkes Kemenkes Yogyakarta, 2014)
Maternal mortality rate of Kalimantan Barat Province is on the 7 in Indonesia, about 353/100.000 birth, which is 2,8% caused by infection. The vigilance of patient service standard is consist of hand hygiene, self-protection equipment, patient care tools, environment control, patient tools and linen processing, worker’s health or health provider safety, and patient placement. Health providers have to apply the infection prevention within patient relationship. Education and training for health provider is one of the way for developing the human resources of health. For doing the professionalism strategy is need to be using competence standard, training and other quality improvement activities.This study was observational analytic designed as cross sectional. As the independent variable (are working period, training participation and education level) and dependent variable (is infection prevention behavior). Research subject are 55 midwives in RSUD dr. Soedarso, taken by Total Sampling. Data has been analyzed using univariate and bivariate analysis by Kendall’s Tau statistic test.Statistic test result showed that there is any correlation between working period and infection prevention behavior (p-value 0,02). There is any correlation between training participation and infection prevention behavior (p-value 0,02). There is any correlation between education level and infection prevention behavior (p-value 0,01).